Anthocyanin From Rosella Petals (Hibiscus sabdariffa L.) as Anion Chemosensory - Syamsu Nur; Imrawati Imrawati; Fitriyanti Jumaetri Sami; Alfat Fadri; Megawati Megawati (Jurnal Farmasi dan Ilmu Pengobatan, 2021)
Rosella plants are a type of hibiscus plant and can be used as a health drink for various diseases. Rosella flowers have the potential to be used as a source of natural dyes in food. The purpose of this study is to determine the anthocyanin of rosella petals as a chemosensory anion compound. To be used as a chemosensory anion compound, testing needs to be done. The ethanol extract of rosella flower petals was extracted by sonication and the filtrate was evaporated to obtain a red extract. From the results of the extract obtained a rendition of 2.9%. Then the extract was tested as an anion chemosensory with the stages of determining the total anthocyanin content, solvatochromic test, and chemosensory test for saturated anions. The total anthocyanin content obtained was 7.648 grams / 100 grams and the chemosensor test results for saturated anions showed a significant change with the addition of KSCN from pink to clear color. Anthocyanin contained in rosella petals can be used as a chemosensor cyanide anion compound.